2019
DOI: 10.1111/bjd.18179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dupilumab treatment in 95 patients with atopic dermatitis: daily practice data

Abstract: Summary Background Dupilumab is the first biologic registered for the treatment of moderate‐to‐severe atopic dermatitis (AD), and efficacy was shown in phase III clinical trials (primary outcome at week 16 was reached in 38% of patients). Currently, there are limited daily practice data available for dupilumab, especially when it is combined with systemic immunosuppressants. Objectives To evaluate dupilumab treatment in daily practice in patients with AD. Methods In this observational cohort study, we prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 41 publications
(130 reference statements)
7
70
1
5
Order By: Relevance
“…Dupilumab was well tolerated in most patients, with only 11.9% of patients suffering from blepharoconjunctivitis, a finding which is in contrast to studies reporting eye symptoms in up to 62% of cases [18]. Although the underlying mechanism of blepharoconjunctivitis in AD patients is still not completely elucidated, some authors have suggested that the blockade of IL-4 and IL-13 may increase the activity of specific ligands, such as OX40 ligand, involved in atopic keratoconjunctivitis [31].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Dupilumab was well tolerated in most patients, with only 11.9% of patients suffering from blepharoconjunctivitis, a finding which is in contrast to studies reporting eye symptoms in up to 62% of cases [18]. Although the underlying mechanism of blepharoconjunctivitis in AD patients is still not completely elucidated, some authors have suggested that the blockade of IL-4 and IL-13 may increase the activity of specific ligands, such as OX40 ligand, involved in atopic keratoconjunctivitis [31].…”
Section: Discussionmentioning
confidence: 87%
“…In this regard, dupilumab (Dupixent ® ), a fully human monoclonal antibody inhibiting the interleukin (IL)-4/IL-13 signaling through the blockade of the IL-4 receptor α subunit, has been recently approved by both the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for the treatment of patients with moderate-to-severe inadequately controlled AD [6]. However, although dupilumab has been demonstrated to be an effective and safe therapeutic option by the two identical phase-3 SOLO1 and SOLO2 trials [7] and the LIBERTY AD CHRONOS [8] and LIBERTY AD CAFÉ [9] phase-3 trials, literature data resulting from a real-life daily practice setting are limited [10][11][12][13][14][15][16][17][18]. Therefore, with the aim of identifying possible predictors of response to dupilumab and assessing the clinical response to this drug in terms of quality of life and disease severity improvement, we retrospectively assessed cases of severe AD treated with dupilumab for a period of at least 16 weeks at our Department.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of new AD treatments to date has been demonstrated primarily in clinical trial settings [25][26][27] rather than in real-life studies. 20,[28][29][30][31][32][33][34] Given the indicators that suggest the use of dupilumab to treat AD, we must now also study the associated atopic comorbidities. Indeed, the European Medicines Agency recently approved the use of dupilumab to treat bronchial asthma Th2 inflammation in patients over 12 years of age, given the failure of CSI/LABA/LAMA as an add-on therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the paper by deWijs et al 3 in this issue of the BJD, the first-year clinical real-life experience with dupilumab, an antiinterleukin (IL)-13/IL-4R antibody, in 95 patients with atopic dermatitis (AD) is described. Patients were recruited from two academic dermatology centres in the Netherlands among patients suffering from moderate-to-severe AD, of whom 62 were already on active systemic immune suppressive therapy.…”
Section: Real-world Evidence Vs Randomized Control Trialsmentioning
confidence: 99%